2014
DOI: 10.1002/lsm.22274
|View full text |Cite
|
Sign up to set email alerts
|

An automatic robotic system for three-dimensional tooth crown preparation using a picosecond laser

Abstract: The ablation experimental results show that the movement range and the resolution of the robotic system can meet the requirements of typical dental operations for tooth crown preparation. Also, the errors of tooth shape and preparation angle are able to satisfy the requirements of clinical crown preparation. Although the experimental results illustrate the potential of using picosecond lasers for 3D tooth crown preparation, many research issues still need to be studied before the system can be applied to clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…For abutment tooth preparation, an ablation system combining robotics and picosecond laser has been developed. In vitro results indicated that the average linear ablation errors of this system were only 0.06 mm for wax resin and 0.05 mm for dentin (Wang et al 2014). However, the long ablation time for dentin (3.5 h) precluded its clinical application.…”
Section: Applications Of Ai In Dentistrymentioning
confidence: 98%
See 1 more Smart Citation
“…For abutment tooth preparation, an ablation system combining robotics and picosecond laser has been developed. In vitro results indicated that the average linear ablation errors of this system were only 0.06 mm for wax resin and 0.05 mm for dentin (Wang et al 2014). However, the long ablation time for dentin (3.5 h) precluded its clinical application.…”
Section: Applications Of Ai In Dentistrymentioning
confidence: 98%
“…Two types of AI are available for general health care delivery: physical and virtual. Physical applications are represented by sophisticated robots or automated robotic arms (Wang et al 2014). Virtual components are software-type algorithms that support clinical decision making.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Disagreement between authors Rekow [25] [29,30,38]. Furthermore, the computer color matching (CCM) technique provides an accurate color matching of dental restorations, together with the automatic laser ablation system for clinical crown preparation [14,44]. Overall, the above methods if introduced into routine practice can be helpful in diagnosis and treating dental diseases.…”
Section: Author and Year Reason Of Exclusionmentioning
confidence: 99%
“…According to the standards described in the Cochrane Handbook for Systematic Reviews of Interventions (v5.1.0) [19], the following findings were recorded. Out of the 32 studies [5][6][7][8][9][10][11][12][13][14][15][16][17][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] assessed, 1 study employed blinding [6]. In 5 studies, randomizations [5,7,34,37,39] were performed.…”
Section: Author and Year Reason Of Exclusionmentioning
confidence: 99%
“…A comparison of another tooth preparation robotic system designed for dental veneers having a rotating diamond tool installed on a robot arm was performed with crown preparation carried out by a human clinician [ 63 ]. The results demonstrated better outcomes in comparison with the crown preparation performed by the clinician with an average repetition ability of the robotic system of around 40 µm [ 64 , 65 ].…”
Section: Robots In Dentistrymentioning
confidence: 99%